Preparation method and application of ion conductive hydrogel

CN117164889BActive Publication Date: 2026-10-27QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310898619.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2026-10-27
Estimated Expiration
2043-07-21

AI Technical Summary

Technical Problem

[0004]然而,现有的水凝胶制作面临以下问题:首先,传统的水凝胶缺乏额外的粘附层,不能与人体皮肤有良好的适配性,这使其用来制备柔性可穿戴传感器变得繁琐

Benefits of technology

(1)本发明提供了一种含有聚硫辛酸、Fe3+离子、海藻酸钠和离子液体的的离子导电水凝胶。通过加热诱导硫辛酸开环聚合形成高分子长链,而离子液体的存在通过形成COOH···O=S氢键阻止了聚硫辛酸的进一步解聚。由于动态相互作用(包括金属配位键、离子键、氢键和静电相互作用)的可逆性,所制备的离子导电水凝胶具有显著的伸长性(应变高达2000%)、自愈合性能(96。37%的愈合效率)和粘附性。此外,离子导电水凝胶具有优异的导电灵敏度(GF=1。31)和快速的响应时间(205s),作为柔性可穿戴电子传感器能够监测和区分人体的大型运动和细微的生理活动。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117164889B_ABST
    Figure CN117164889B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of polymer hydrogel, and particularly relates to a preparation method of ion-conducting hydrogel and application thereof, and comprises the following steps: S1, preparing an iron citrate solution by mixing iron nitrate nonahydrate and sodium citrate dihydrate in deionized water, and then adjusting the pH value to 6-7 by using a sodium hydroxide solution, denoted as A liquid; S2, dissolving tris(hydroxymethyl)aminomethane in deionized water, then adding a certain amount of sodium alginate into the solution, vortexing and ultrasonicating until the solution is uniform; then, adding alpha-lipoic acid into the solution under stirring and ultrasonicating to obtain a yellow solution; finally, adding a certain volume of ionic liquid into the alpha-lipoic acid solution and stirring for 3 minutes, denoted as B liquid; pouring the B liquid into a mold, heating at 80 DEG C in an oven for 1.5 h, and forming a pre-gel after cooling at room temperature; S3, uniformly dissolving the pre-gel obtained in the step B into the A liquid, and placing for several days to promote the formation of uniform coordination sites, and then heating to evaporate excess water, and forming an ion-conducting hydrogel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer hydrogel technology, and particularly relates to a method for preparing ion-conducting hydrogels and their applications. Background Technology

[0002] In recent years, with the development of the Internet of Things (IoT), the connection between electronic sensing devices and physical objects has become increasingly important. Wearable electronic sensing devices have attracted much attention due to their ability to conveniently detect human movement and physiological signals. Traditional wearable electronic sensing devices typically combine conductive materials with flexible substrates, adhering them to the human body surface through external means to detect human movement and physiological signals. However, traditional wearable electronic sensing devices are usually rigid and brittle, unable to withstand significant tensile deformation, and have poor skin compatibility, which is detrimental to the long-term stability of the sensing devices.

[0003] Ionically conductive hydrogels have wide applications in artificial intelligence, biomedical detection, electronic skin, soft robotics, and flexible wearable devices due to their flexibility, high water retention, biocompatibility, and highly sensitive conductivity. To date, most reported conductive hydrogels have been prepared by incorporating carbon nanotubes (CNTs), silver nanowires (AgNWs), graphene oxide (GO), ionic liquids (ILs), and conductive polymers (polyaniline, polypyrrole) into the hydrogel. Among these, the strategy of combining hydrogels with ionic liquids shows great potential for fabricating flexible wearable electronic devices based on ionically conductive hydrogels. This is because the resulting flexible electronic devices exhibit high ionic conductivity, biocompatibility, and good chemical stability; more importantly, their functions and properties can be customized by adjusting the structure of paired cations and anions in the IL.

[0004] However, existing hydrogel fabrication methods face the following challenges: First, traditional hydrogels lack an additional adhesive layer and do not adapt well to human skin, making their use in the fabrication of flexible wearable sensors cumbersome. Second, traditional hydrogels are typically single-network hydrogels formed by free radical polymerization. This process may involve toxic monomers, cross-linking agents, initiators, and an anaerobic environment, potentially leading to limited green production and difficulty in recycling. This increases costs and pollutes the environment, which is detrimental to large-scale production and construction. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing ion-conducting hydrogels and their applications.

[0006] This invention reports the preparation of a low-toxicity, highly conductive hydrogel by thermal ring-opening polymerization of the natural small molecule α-lipoic acid and cross-linking it with the natural polysaccharide sodium alginate in the presence of an aqueous solvent, through careful adjustment of the internal interactions within the polylipoic acid elastomer. Furthermore, iron (III) ions are introduced into the network, acting as strong complex centers with carboxyl groups, replacing some weak hydrogen bonds and forming stronger metal coordination bonds. Therefore, polylipoic acid, sodium alginate, and iron (III) ions together form a thermodynamically stable supramolecular poly(lipoic acid-sodium alginate-Fe...) 3+ A copolymer network was constructed. Furthermore, the addition of an air-stabilized ionic liquid to the multi-layered network to form hydrogen bonds between the liquid and the carboxylic acid effectively stabilized the polymerized poly(lipoic acid). The prepared poly(lipoic acid-sodium alginate-Fe) copolymer network... 3+ The copolymer-based ion-conductive hydrogel possesses various types of dynamic chemical bonds, including dynamic covalent disulfide bonds, iron(III)-carboxyl coordination bonds, non-covalent bonds, and ionic bonds. The resulting copolymer material exhibits excellent properties such as stretchability, recyclability, self-adhesion, self-healing ability, and outstanding conductivity. This non-toxic, biocompatible hydrogel can be used in flexible wearable electronic sensors to monitor human movement and subtle physiological activities, including large and small movements such as finger flexion, wrist flexion, smiling, swallowing, and vocalization recognition.

[0007] The technical solution adopted in this invention is: This invention provides a method for preparing an ion-conducting hydrogel, comprising the following preparation steps: Step S1: Preparation of ferric citrate solution Ferric citrate solution was prepared by mixing ferric nitrate nonahydrate and sodium citrate dihydrate in deionized water. The pH of the mixed solution was then adjusted to between 6 and 7 using 5 mol / L sodium hydroxide solution. This solution was denoted as solution A. Step S2: Preparation of hydrogel pregelation solution Dissolve tris(hydroxymethyl)aminomethane in deionized water, then add a certain amount of sodium alginate to the solution, vortex and sonicate until the solution is homogeneous; Next, α-lipoic acid was added to the solution under stirring and sonication to obtain a yellow solution; Finally, a certain volume of ionic liquid was added to the α-lipoic acid solution and stirred for 3 minutes, which was recorded as solution B. Pour liquid B into a mold and heat in an oven at 80°C for 1.5 hours. After cooling to room temperature, a pre-gel is formed. Step S3: Formation of ion-conducting hydrogel The pregel obtained from solution B in step B is uniformly dissolved in solution A and left to stand for several days to promote the formation of uniform coordination sites. Then, it is heated to evaporate excess water to form an ion-conducting hydrogel.

[0008] Based on the above scheme, furthermore, in step one, the molar ratio of ferric nitrate nonahydrate to sodium citrate dihydrate is 1:1.

[0009] Based on the above scheme, further, in step two, the mass ratio of α-lipoic acid to sodium alginate is (35~40):1.

[0010] Based on the above scheme, further, in step two, the mass ratio of tris(hydroxymethyl)aminomethane to deionized water is 1:4.

[0011] Based on the above scheme, further, in step two, the mass ratio of deionized water to α-lipoic acid is 2:1.

[0012] Based on the above scheme, further, in step two, the molar ratio of α-lipoic acid to ionic liquid is (4~10):1.

[0013] Based on the above scheme, further, in step three, the molar ratio of α-lipoic acid to ferric ions is 1:(0.5%~5%).

[0014] Based on the above scheme, further, the ionic liquid in step two is one or more of 1-ethyl-3-methylimidazolium sulfate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium trifluoromethanesulfonate and 1-butyl-3-methylimidazolium tetrafluoroborate.

[0015] The present invention provides an ion-conducting hydrogel prepared by the aforementioned preparation method.

[0016] This invention provides the application of ion-conductive hydrogels in the fabrication of flexible wearable electronic sensors.

[0017] Furthermore, the prepared ion-conductive hydrogel can be cut into any shape according to self-requirement, directly adhered to human skin, and then connected to electrodes for large and small-scale motion detection of the human body.

[0018] Furthermore, the flexible wearable electronic device prepared in step four can be made into any shape according to one's own requirements, such as rectangle, circle, fan shape, etc.

[0019] By adopting the above technical solution, the present invention has the following advantages and beneficial effects: (1) The present invention provides a solution containing polythioctic acid and Fe 3+Ionic conductive hydrogels based on ions, sodium alginate, and ionic liquids were developed. Heating induced the ring-opening polymerization of polylipoic acid to form long polymer chains, while the presence of the ionic liquid prevented further depolymerization of polylipoic acid through the formation of COOH···O=S hydrogen bonds. Due to the reversibility of dynamic interactions (including metal coordination bonds, ionic bonds, hydrogen bonds, and electrostatic interactions), the prepared ionic conductive hydrogels exhibit significant elongation (strain up to 2000%), self-healing properties (healing efficiency of 96.37%), and adhesion. Furthermore, the ionic conductive hydrogels possess excellent conductivity sensitivity (GF = 1.31) and a fast response time (205 s), making them suitable as flexible wearable electronic sensors to monitor and distinguish between large-scale human movements and subtle physiological activities.

[0020] (2) Ion-conductive hydrogels can be completely recycled and reused without significant loss of their original functions through simple dissolution and solvent evaporation, which has broad prospects for reducing electronic waste that seriously pollutes the environment. This ion-conductive hydrogel with multiple synergistic functions is expected to provide a new approach for people to develop ideal green flexible wearable electronic sensors.

[0021] (3) This invention endows the simple bio-based small molecule material with high mechanical properties through multiple hydrogen bond interactions with natural polysaccharides and coordination complexation with iron ions, while the addition of ionic liquids imparts high conductivity. The ion-conductive hydrogel can be recycled and reused multiple times without losing its original properties, and it can also self-heal at room temperature after being scratched or damaged. In addition, the resulting ion-conductive hydrogel can directly adhere to the human body surface, thereby recording and recognizing different sizes of human body movements. Attached Figure Description

[0022] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the accompanying drawings used in the description of the specific embodiments or the prior art will be briefly introduced below.

[0023] Figure 1 This is a schematic diagram of the preparation process and internal structure of the ion-conducting hydrogel (the ionic liquid used is ethyl 1-ethyl-3-methylimidazolium sulfate).

[0024] Figure 2 This is the Raman spectrum of an ion-conducting hydrogel.

[0025] Figure 3 This is a graph showing the tensile properties of an ion-conductive hydrogel.

[0026] (3a) Fe with different mole fractions 3+ Stress-strain distribution of conductive hydrogels with ions (stretching speed = 500 mm / min).

[0027] (3b) Tensile strain, toughness and strength changes of conductive hydrogels.

[0028] (3c) Tensile stress-strain curves of conductive hydrogels with different amounts of ionic liquid added (strain rate = 500 mm / min).

[0029] Figure 4 This is a test diagram of the adhesive properties of conductive hydrogels.

[0030] (4a) Adhesion of conductive hydrogels on different substrates.

[0031] (4b) Schematic diagram and actual object of conductive hydrogel overlap.

[0032] (4c) Maximum shear bond strength of conductive hydrogel on different substrates.

[0033] (4d) The conductive hydrogel was subjected to five cycles of repeated shear stress tests on five different substrates (paper, wood, steel, rubber and plastic).

[0034] Figure 5 The rapid self-healing ability of conductive hydrogels, including electrical signals and mechanical properties.

[0035] (5a) The self-healing ability of conductive hydrogels was observed macroscopically by shearing, contacting and stretching stained and unstained hydrogels.

[0036] (5b) Electrical signal repair demonstrated by the change in brightness of an LED bulb (connected to a battery) before and after self-healing.

[0037] (5c) Ultra-depth optical microscopy images of self-healing hydrogels during cutting and self-healing processes.

[0038] (5d) Tensile stress-strain curves of conductive hydrogels after healing at room temperature for different times.

[0039] (5e) Self-healing efficiency at room temperature from 20 min to 120 min.

[0040] (5f) Current recovery of the conductive hydrogel during the tangent-closing cycle.

[0041] Figure 6 The figure shows the results of the recyclability test for the conductive hydrogel.

[0042] (6a) Schematic diagram of the recyclability of conductive hydrogel.

[0043] (6b) Stress-strain curves of the original and recycled conductive hydrogels.

[0044] (6c) Changes in Young's modulus before and after recycling.

[0045] (6d) Schematic diagram of conductive hydrogel being reshaped into different shapes.

[0046] (6f) Changes in conductivity before and after recycling.

[0047] Figure 7 This is a schematic diagram of the resistive response of a conductive hydrogel to large strain when it is attached to the skin. (7a) The step response of the sensor to the relative change in resistance as the finger flexion angle increases. The change in the relative resistance of the hydrogel sensor over time during the periodic movements of (7b) wrist flexion, (7c) elbow flexion, and (7d) knee flexion (standing and sitting).

[0048] Figure 8 This is a schematic diagram of the resistive response of a conductive hydrogel to small strain when it is attached to the skin.

[0049] (8a) A conductive hydrogel was attached to the neck to test its response to swallowing behavior.

[0050] (8b) Frowning and calmness and (8c) puffing out and calmness of the face show periodic changes in relative resistance. (8d) Smiling and calm expressions (distinguishing between a slight smile and a big laugh) and (8e) calmness of the eyes show periodic changes in relative resistance.

[0051] (8f) The hydrogel sensor recognizes signals from volunteers speaking different words (including apple, banana, zi, thank you and hello). Detailed Implementation

[0052] The present invention will be described in detail below with reference to embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several adjustments and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0053] Example 1 Step S1: Preparation of ferric citrate solution Ferric citrate solution was prepared by mixing ferric nitrate nonahydrate and sodium citrate dihydrate in deionized water at a molar ratio of 1:1. The pH of the mixed solution was then adjusted to between 6 and 7 using 5 mol / L sodium hydroxide solution, and this solution was designated as solution A. Step S2: Preparation of hydrogel pregelation solution Dissolve 2.25g of tris(hydroxymethyl)aminomethane in 9mL of deionized water, then add 120mg of sodium alginate to the solution, vortex and sonicate until the solution is homogeneous; Next, 4.5 g of α-lipoic acid was added to the solution under stirring and sonication to obtain a yellow solution; Finally, 5.45 mmol of ionic liquid was added to the α-lipoic acid solution and stirred for 3 minutes, denoted as solution B; solution B was poured into a mold and heated in an oven at 80°C for 1.5 h, and after cooling to room temperature, a pregel was formed; Step S3: Formation of ion-conducting hydrogel The pregel obtained from solution B in step B above was uniformly dissolved in solution A, wherein the molar amount of ferric ions was 0.11 mmol. The solution was left to stand for several days to promote the formation of uniform coordination sites, and then heated to evaporate excess water to form an ion-conducting hydrogel.

[0054] Example 2 Step S1: Preparation of ferric citrate solution Ferric citrate solution was prepared by mixing ferric nitrate nonahydrate and sodium citrate dihydrate in deionized water at a molar ratio of 1:1. The pH of the mixed solution was then adjusted to between 6 and 7 using 5 mol / L sodium hydroxide solution, and this solution was designated as solution A. Step S2: Preparation of hydrogel pregelation solution Dissolve 2.25g of tris(hydroxymethyl)aminomethane in 9mL of deionized water, then add 120mg of sodium alginate to the solution, vortex and sonicate until the solution is homogeneous; Next, 4.5 g of α-lipoic acid was added to the solution under stirring and sonication to obtain a yellow solution; Finally, 5.45 mmol of ionic liquid was added to the α-lipoic acid solution and stirred for 3 minutes, denoted as solution B; solution B was poured into a mold and heated in an oven at 80°C for 1.5 h, and after cooling to room temperature, a pregel was formed; Step S3: Formation of ion-conducting hydrogel The pregel obtained from solution B in step B above was uniformly dissolved in solution A, wherein the molar amount of ferric ions was 0.22 mmol. The solution was left to stand for several days to promote the formation of uniform coordination sites, and then heated to evaporate excess water to form an ion-conducting hydrogel.

[0055] Example 3 Step S1: Preparation of ferric citrate solution Ferric citrate solution was prepared by mixing ferric nitrate nonahydrate and sodium citrate dihydrate in deionized water at a molar ratio of 1:1. The pH of the mixed solution was then adjusted to between 6 and 7 using 5 mol / L sodium hydroxide solution, and this solution was designated as solution A. Step S2: Preparation of hydrogel pregelation solution Dissolve 2.25g of tris(hydroxymethyl)aminomethane in 9mL of deionized water, then add 120mg of sodium alginate to the solution, vortex and sonicate until the solution is homogeneous; Next, 4.5 g of α-lipoic acid was added to the solution under stirring and sonication to obtain a yellow solution; Finally, 5.45 mmol of ionic liquid was added to the α-lipoic acid solution and stirred for 3 minutes, denoted as solution B; solution B was poured into a mold and heated in an oven at 80°C for 1.5 h, and after cooling to room temperature, a pregel was formed; Step S3: Formation of ion-conducting hydrogel The pregel obtained from solution B in step B above was uniformly dissolved in solution A, wherein the molar amount of ferric ions was 0.33 mmol. The solution was left to stand for several days to promote the formation of uniform coordination sites, and then heated to evaporate excess water to form an ion-conductive hydrogel.

[0056] Example 4 Step S1: Preparation of ferric citrate solution Ferric citrate solution was prepared by mixing ferric nitrate nonahydrate and sodium citrate dihydrate in deionized water at a molar ratio of 1:1. The pH of the mixed solution was then adjusted to between 6 and 7 using 5 mol / L sodium hydroxide solution, and this solution was designated as solution A. Step S2: Preparation of hydrogel pregelation solution Dissolve 2.25g of tris(hydroxymethyl)aminomethane in 9mL of deionized water, then add 120mg of sodium alginate to the solution, vortex and sonicate until the solution is homogeneous; Next, 4.5 g of α-lipoic acid was added to the solution under stirring and sonication to obtain a yellow solution; Finally, 5.45 mmol of ionic liquid was added to the α-lipoic acid solution and stirred for 3 minutes, denoted as solution B; solution B was poured into a mold and heated in an oven at 80°C for 1.5 h, and after cooling to room temperature, a pregel was formed; Step S3: Formation of ion-conducting hydrogel The pregel obtained from solution B in step B above was uniformly dissolved in solution A, wherein the molar amount of ferric ions was 0.44 mmol. The solution was left to stand for several days to promote the formation of uniform coordination sites, and then heated to evaporate excess water to form an ion-conductive hydrogel.

[0057] Example 5 Step S1: Preparation of ferric citrate solution Ferric citrate solution was prepared by mixing ferric nitrate nonahydrate and sodium citrate dihydrate in deionized water at a molar ratio of 1:1. The pH of the mixed solution was then adjusted to between 6 and 7 using 5 mol / L sodium hydroxide solution, and this solution was designated as solution A. Step S2: Preparation of hydrogel pregelation solution Dissolve 2.25g of tris(hydroxymethyl)aminomethane in 9mL of deionized water, then add 120mg of sodium alginate to the solution, vortex and sonicate until the solution is homogeneous; Next, 4.5 g of α-lipoic acid was added to the solution under stirring and sonication to obtain a yellow solution; Finally, 5.45 mmol of ionic liquid was added to the α-lipoic acid solution and stirred for 3 minutes, denoted as solution B; solution B was poured into a mold and heated in an oven at 80°C for 1.5 h, and after cooling to room temperature, a pregel was formed; Step S3: Formation of ion-conducting hydrogel The pregel obtained from solution B in step B above was uniformly dissolved in solution A, wherein the molar amount of ferric ions was 0.55 mmol. The solution was left to stand for several days to promote the formation of uniform coordination sites, and then heated to evaporate excess water to form an ion-conducting hydrogel.

[0058] Examples 1-5 show the control of the molar amount of added ferric ions.

[0059] Example 6 Step S1: Preparation of ferric citrate solution Ferric citrate solution was prepared by mixing ferric nitrate nonahydrate and sodium citrate dihydrate in deionized water at a molar ratio of 1:1. The pH of the mixed solution was then adjusted to between 6 and 7 using 5 mol / L sodium hydroxide solution, and this solution was designated as solution A. Step S2: Preparation of hydrogel pregelation solution Dissolve 2.25g of tris(hydroxymethyl)aminomethane in 9mL of deionized water, then add 120mg of sodium alginate to the solution, vortex and sonicate until the solution is homogeneous; Next, 4.5 g of α-lipoic acid was added to the solution under stirring and sonication to obtain a yellow solution; Finally, 2.18 mmol of ionic liquid was added to the α-lipoic acid solution and stirred for 3 minutes, denoted as solution B; solution B was poured into a mold and heated in an oven at 80°C for 1.5 h, and after cooling to room temperature, a pregel was formed; Step S3: Formation of ion-conducting hydrogel The pregel obtained from solution B in step B above was uniformly dissolved in solution A, wherein the molar amount of ferric ions was 0.33 mmol. The solution was left to stand for several days to promote the formation of uniform coordination sites, and then heated to evaporate excess water to form an ion-conductive hydrogel.

[0060] Example 7 Step S1: Preparation of ferric citrate solution Ferric citrate solution was prepared by mixing ferric nitrate nonahydrate and sodium citrate dihydrate in deionized water at a molar ratio of 1:1. The pH of the mixed solution was then adjusted to between 6 and 7 using 5 mol / L sodium hydroxide solution, and this solution was designated as solution A. Step S2: Preparation of hydrogel pregelation solution Dissolve 2.25g of tris(hydroxymethyl)aminomethane in 9mL of deionized water, then add 120mg of sodium alginate to the solution, vortex and sonicate until the solution is homogeneous; Next, 4.5 g of α-lipoic acid was added to the solution under stirring and sonication to obtain a yellow solution; Finally, 2.73 mmol of ionic liquid was added to the α-lipoic acid solution and stirred for 3 minutes, denoted as solution B; solution B was poured into a mold and heated in an oven at 80°C for 1.5 h, and after cooling to room temperature, a pregel was formed; Step S3: Formation of ion-conducting hydrogel The pregel obtained from solution B in step B above was uniformly dissolved in solution A, wherein the molar amount of ferric ions was 0.33 mmol. The solution was left to stand for several days to promote the formation of uniform coordination sites, and then heated to evaporate excess water to form an ion-conductive hydrogel.

[0061] Example 8 Step S1: Preparation of ferric citrate solution Ferric citrate solution was prepared by mixing ferric nitrate nonahydrate and sodium citrate dihydrate in deionized water at a molar ratio of 1:1. The pH of the mixed solution was then adjusted to between 6 and 7 using 5 mol / L sodium hydroxide solution, and this solution was designated as solution A. Step S2: Preparation of hydrogel pregelation solution Dissolve 2.25g of tris(hydroxymethyl)aminomethane in 9mL of deionized water, then add 120mg of sodium alginate to the solution, vortex and sonicate until the solution is homogeneous; Next, 4.5 g of α-lipoic acid was added to the solution under stirring and sonication to obtain a yellow solution; Finally, 3.64 mmol of ionic liquid was added to the α-lipoic acid solution and stirred for 3 minutes, denoted as solution B; solution B was poured into a mold and heated in an oven at 80°C for 1.5 h, and after cooling to room temperature, a pregel was formed; Step S3: Formation of ion-conducting hydrogel The pregel obtained from solution B in step B above was uniformly dissolved in solution A, wherein the molar amount of ferric ions was 0.33 mmol. The solution was left to stand for several days to promote the formation of uniform coordination sites, and then heated to evaporate excess water to form an ion-conductive hydrogel.

[0062] Examples 3 and 6-8 show the control of the amount of ionic liquid added.

[0063] Comparative Example 1 The conditions for Comparative Example 1 and Example 1 are the same, except that ferric ions are not added in Comparative Example 1.

[0064] Results and discussion (1) Structural characterization Raman spectra were recorded on a laser confocal Raman spectrometer (model: RenishawinVia) with an excitation wavelength of 532 nm.

[0065] Figure 2 It showcased ingredients containing α-lipoic acid, sodium alginate, and Fe. 3+ Preparation process of ion-conducting hydrogels with 1-ethyl-3-methylimidazolium sulfate network.

[0066] Figure 1 This is a schematic diagram of the Raman spectrum of the ion-conducting hydrogel. It can be seen that α-lipoic acid underwent thermally initiated dynamic ring-opening polymerization via dynamic disulfide bond exchange through layered self-assembly of disulfide bonds containing a five-membered ring. The characteristic peak of the disulfide bond is observed from 511 cm⁻¹. -1 The Raman peak at that location splits, and at 509cm... -1 and 524cm -1 Two new characteristic peaks appeared at the point. Based on the above conclusions, the formation of polymer composite materials can be achieved using... Figure 2 The preparation process of the ion-conductive hydrogel is illustrated in the schematic diagram. First, the α-lipoic acid monomer undergoes thermally initiated ring-opening polymerization via disulfide bond exchange, forming a primary linear covalent backbone linked by dynamic disulfide bonds. Then, the ionic liquid can form COOH···O=S hydrogen bonds with the hydroxyl groups on the main chain, thereby inhibiting further depolymerization of poly-α-lipoic acid. Simultaneously, sodium alginate can form intermolecular hydrogen bonds with the side chains of polylipoic acid and also form ionic interactions with 1-ethyl-3-methylimidazolium sulfate. Furthermore, polylipoic acid and sodium alginate can contribute their acidic groups to react with Fe... 3+ The formation of metal-ligand coordination bonds enhances the mechanical strength and conductivity of supramolecular hydrogels. Therefore, in the preparation of ion-conductive hydrogels, a hierarchical polymer network consisting of dynamic disulfide bonds, intermolecular hydrogen bonds, metal coordination bonds, and ionic bonds was successfully obtained. It is precisely these dynamic, reversible bonds formed by numerous intermolecular interactions within the hydrogel that endow it with excellent mechanical properties such as self-healing. (2) Mechanical performance testing Tensile tests were performed at room temperature using a universal testing machine (Instron 5963). The samples were prepared into rectangular shapes (scale: 50 mm x 15 mm x 2 mm) and then used for tensile testing, with the strain rate fixed at 500 mm / min.

[0067] Figure 2 The physical and mechanical properties of ion-conductive hydrogels were demonstrated. Figure 3 a studied Fe 3+ The effect of ions on the mechanical strength of ion-conducting hydrogels, noting the strong non-covalent crosslinking (Fe). 3+ -Carboxyl coordination bonds have a significant impact on the shrinkability and mechanical strength of ion-conducting hydrogels. Compared with other supramolecular gels, Comparative Example 1 does not contain Fe. 3+ It exhibits poor mechanical properties but still maintains its shape and high tensile strength. As can be seen from the figure, with Fe... 3+ With increasing ion content, the tensile strength and tensile strain of ion-conducting hydrogels also increase, exhibiting higher Fe content. 3+ Example 3, with an ion content of 0.33 mmol, exhibited the most stable and robust mechanical structure, with a tensile strength of 1700% and high mechanical strength observed. However, further increases in Fe... 3+ With increasing ion content (0.55 mmol), the mechanical strength of the hydrogel gradually weakens. A possible explanation for this is that excessive Fe... 3+ This may affect the polymerization of thioctic acid chains, resulting in the presence of non-crosslinked ions in the gel, thus adversely affecting mechanical properties. Therefore, an appropriate amount of Fe was found... 3+ To improve the crosslinking rate, while maintaining high ductility, mechanical strength is balanced.

[0068] like Figure 3 As shown in b, the area under the stress-strain curve was used to calculate the values ​​of different Fe values. 3+ The content of hydrogel toughness and tensile strength, initially, without Fe 3+ The toughness of Comparative Example 1 is 120.78 KJ / m. 3 Its strength is 14.23 kPa, while with Fe... 3+ The content increased from 0.11 to 0.55, and the toughness increased from 309.02 KJ / m. 3 Increased to 389.72 kJ / m 3 The strength increased from 17.83 kPa to 25.31 kPa, indicating that Fe... 3+ -Carboxyl coordination bonds play a crucial role. Further increasing Fe... 3+ The content of [specific element] decreased, and the toughness and strength of the hydrogel dropped to 248.38 KJ / m. 3 And 23.79 kPa.

[0069] Figure 3 c shows the tensile stress-strain curves of the ion-conducting hydrogels obtained in Examples 3 and 5-7, and investigates the effect of the amount of ion liquid on the mechanical properties. Figure 3As shown in Figure c, all polythiooctanoic acid ionomers exhibit high elongation, and their mechanical properties in terms of elongation, modulus, and tensile strength can be adjusted by simply changing the amount of ionic liquid to meet different application requirements. When the ionic liquid content is increased from 2.18 mmol / mol to 5.45 mmol / mol, the tensile properties of the hydrogel are significantly improved, but the strength is significantly reduced.

[0070] (3) Adhesion test of ion-conducting hydrogel To better demonstrate the excellent adhesion behavior of the hydrogel, the hydrogel prepared in Example 3 was bonded to different substrates such as glass, steel, PTFE, paper, leather, and rubber. Figure 4 a) It was found that the ion-conductive hydrogel exhibited high adhesion without the need for any additional adhesive layer. More importantly, the hydrogel exhibited strong tissue adhesion, allowing it to adhere directly to human skin, which is beneficial for more effective monitoring of human joint movement.

[0071] To determine the adhesion strength of the hydrogel on different substrates, a quantitative lap shear test was conducted on the hydrogel sandwiched between the surfaces of different substrates. Figure 4 b). Then, the surface is stretched using a tensile testing machine until separation or fracture occurs, resulting in a hydrogel bonded to glass. The maximum adhesive strengths to steel, PTFE, paper, leather, rubber, PET, and plastics are 32.97, 35.24, 10.98, 60.32, 24.35, 29.31, and 53.14 kPa, respectively. Figure 4 c). For example Figure 4 As shown in Figure d, to demonstrate the repeatability and durability of the hydrogel, five repeated cyclic tensile-lap shear tests were conducted on a specific surface of the substrate. It can be seen that after five adhesion-deadlock cycles, the adhesive strength did not decrease significantly, remaining above 95% of its initial strength. The excellent repeatability of the ion-conductive hydrogel can be attributed to two reasons. First, the hydrogel contains a large number of functional groups (such as carboxyl and hydroxyl groups), which can form hydrogen bonds, ion interactions, and ion-dipole interactions with the substrate surface, enabling strong adhesion between the hydrogel and the substrate through reversible interactions. Second, the hydrogel can fully repair damage after unloading, thus rapidly self-recovering and achieving good repeatability. Therefore, the hydrogel can be used for human body-attached sensors to obtain accurate signals without the need for an additional adhesive layer.

[0072] (4) Characterization of self-healing properties Self-healing capability is an important characteristic of ion-conducting hydrogels because it helps extend the lifespan of sensors. In this section, the self-healing property of the hydrogel in Example 3 is used as an example. Figure 5As shown in Figure a, to more intuitively demonstrate the self-healing ability of the hydrogel, it was divided into two parts: one stained with methylene blue, and the other displaying its natural color. The two types of hydrogels were placed together and touched for 30 seconds without any external stimuli, then stretched by hand. The result showed that the healed hydrogel could be further stretched without breaking at the joint. This indicates that the dynamic reversible network within the hydrogel gives it excellent self-healing properties. The restoration of light bulb illumination was also used to demonstrate these self-healing characteristics. Figure 5 (b) Connecting the ion-conducting hydrogel to a simple 6V series circuit revealed that the hydrogel could illuminate a light bulb. Because sodium ions and ionic liquid were introduced into the hydrogel, the directional movement of ions when current passed through it made the hydrogel conductive. When the hydrogel was cut off, the bulb went out; upon re-contact, the bulb immediately lit up again, with its brightness remaining essentially unchanged. The results showed that when the hydrogel was cut off, the resistance instantaneously became infinite (air resistance is infinite), and the current in the path became zero. After re-contact, the current through the hydrogel recovered to its initial value within 0.5 seconds. Figure 5 f). The ultrafast mechanical self-healing property of the hydrogel in Example 3 was observed using a super-depth-of-field optical microscope. The results showed that the incision scar almost completely disappeared after the hydrogel healed, demonstrating good self-healing ability. Figure 5 c). Figure 5 Figure d depicts the stress-strain curves of the hydrogels prepared in Example 3 with different healing times. After healing, the tensile strength and elongation of the hydrogels gradually recovered to their initial state with increasing healing time. As the healing time increased from 20 min to 2 h, the corresponding healing efficiency significantly increased from 33.62% to nearly 100%. Figure 5 e) This demonstrates the material's excellent mechanical self-healing ability. The superior self-healing properties can be attributed to the fact that during the self-healing process, hydrogen bonds and coordination bonds first recombine with the aid of the movement of lipoic acid molecular chain segments, leading to the rapid restoration of the conduction pathway. Therefore, the healing ability of the ion-conducting hydrogel far exceeds its mechanical properties. Then, the dynamic disulfide bonds further recombine along the migration direction of the polymer chains, effectively promoting the reconstruction of the polymer network. Based on the above research, this hydrogel, with its highly stretchable, repairable, and conductive properties, is ideally suited for use as an ion conductor in various functional applications.

[0073] (5) Recyclability of ion-conducting hydrogels The development of recyclable materials offers a promising approach to solving e-waste pollution. Most hydrogels typically require the introduction of chemical cross-linking agents during their preparation, which hinders material recycling and the processing of hydrogels with complex shapes. This not only limits the application of hydrogels in certain fields but also results in significant material waste. Hydrogels, however, utilize the advantage of small-molecule α-lipoic acid undergoing heating to open rings, forming long polymer chains, and then cross-linking with natural polymers to create a dual network, thus preparing hydrogels without cross-linking agents. Due to the dynamic properties of non-covalent interactions, the prepared hydrogels not only possess excellent mechanical properties but are also soluble in solvents, facilitating processing and recycling. Figure 6 As shown in a and 6d, the hydrogel prepared in Example 3 can be completely dissolved in a small amount of water. The dissolved copolymer aqueous solution can be poured into a mold of a specific shape and then dried with a solvent to form hydrogels of different shapes such as pentagrams, snails, and conches. These hydrogels can be recycled multiple times through dissolution, pouring, and drying. Figure 6 d) This aligns with the principle of green and efficient material utilization. The hydrogel prepared in Example 3 still exhibits high stress-strain strength and Young's modulus after multiple recycling cycles. Figure 6 The stress-strain curves in b show that, compared to the initial hydrogel, the tensile strength and tensile properties of the hydrogel after three cycles did not decrease significantly, and the Young's modulus of the recovered hydrogel remained close to that of the initial state. Figure 6 c). The mechanical strength and Young's modulus of the recycled ion-conducting hydrogel did not change significantly, indicating that the material is stable and recyclable. Furthermore, the conductivity of the hydrogel prepared in Example 3 after recycling recovered to over 95% of the original sample, indicating that the recycled hydrogel prepared in Example 3 still possesses high conductivity. Figure 6 e). Therefore, it can be concluded that the hydrogel prepared in Example 3 is feasible for use in green flexible wearable electronic sensors.

[0074] (6) Real-world demonstration as a wearable sensor An ion-conductive hydrogel strain sensor was directly attached to the skin surface, and the corresponding electrical signals were recorded using a KEITHLEY digital source meter to monitor the dynamic process of limb movement (large strain). Figure 7 Hydrogels can adhere firmly to the skin surface without any adhesives for motion detection. Figure 7As shown in Figure a, when the finger flexion angle increases from 30° to 90°, the relative resistance signal increases accordingly and immediately returns to the initial state when the finger is straightened, indicating that the ion-conductive hydrogel strain sensor has high sensitivity. Similarly, due to the different flexion-stretch deformations of different joints, the ion-conductive hydrogel strain sensor can also clearly identify the flexion-stretch behavior of the wrist, elbow, and knee (standing and sitting). Figure 7 Even after extreme deformation, the ion-conductive hydrogel strain sensor repeatedly detects motion. After tension release, the resistance of the ion-conductive hydrogel strain sensor returns to its initial state, and the relative resistance curve shows no significant shift even under repeated deformation. This indicates that the ion-conductive hydrogel strain sensor exhibits good regularity, strong reproducibility, and a stable baseline.

[0075] Ion-conductive hydrogel strain sensors are not only effective at detecting large deformations such as joint movements, but also highly sensitive to minute facial deformations. In a swallowing test, the ion-conductive hydrogel strain sensor was adhered to the throat of a volunteer. The sensor clearly recorded each swallowing motion, and the obtained signal waveforms were essentially identical. Figure 8 a). Adhesive to the eyebrows, the sensor can detect each frown in real time. Figure 8 b). Adhesive to the face, the sensor can clearly detect facial protrusions, obtaining signals during each puff and calm. Figure 8 c). The sensor can also detect each blink of the volunteer, clearly obtaining the speed of the blinking action. Figure 8 d). Furthermore, when the sensor is attached to the cheek, it can clearly capture the volunteer's smiling movements and distinguish between a slight smile and a full laugh. Figure 8 e). Sensors can also be attached to the throat to detect vocal cord vibrations during phonation, such as... Figure 8 As shown in f, different pronunciations result in different signal peak shapes: "Apple" and "Banana" produce narrow, low-amplitude peaks; "Orange" produces a large-amplitude but narrow peak; and "Thank you" and "Hello" produce wide, large-amplitude peaks. In summary, these results verify that the ion-conductive hydrogel strain sensor possesses excellent sensitivity and stability, capable of distinguishing not only large-scale human movements (large deformations) but also accurately detecting subtle changes in facial expressions. Therefore, PLA-Fe-SA ion-conductive hydrogel is a promising green, flexible, wearable strain sensor material.

[0076] This invention yields an easily prepared ion-conducting hydrogel by constructing a hierarchical polymer network composed of disulfide bonds, hydrogen bonds, ionic bonds, and coordination bonds. This preparation method is simple, low-cost, and rapid, especially considering its bio-based material composition. Utilizing various intermolecular interactions, the prepared ion-conducting hydrogel exhibits significant elongation (up to 2000%), excellent self-healing ability (healing efficiency 96.37%), and strong adhesion, making it an ideal candidate for green, flexible wearable electronic sensors. Notably, the ion-conducting hydrogel can be completely recovered and reused through simple dissolution and solvent evaporation without significant loss of its original functionality. Furthermore, the prepared ion-conducting hydrogel demonstrates excellent strain sensitivity (response time 205 s) and repeatability, enabling the monitoring of various large-strain movements in the human body (such as joint movements) as well as accurate measurement of minute strains (such as facial micro-expression changes). Due to its multiple superior properties, the prepared ion-conducting hydrogel is a sustainable and promising functional material with broad development potential in green flexible sensors and intelligent robot manufacturing.

Claims

1. A method for preparing an ion-conducting hydrogel, characterized in that: The preparation steps include the following: Step S1: Preparation of ferric citrate solution Ferric citrate solution was prepared by mixing ferric nitrate nonahydrate and sodium citrate dihydrate in deionized water. The pH of the mixed solution was then adjusted to between 6 and 7 using 5 mol / L sodium hydroxide solution. This solution was denoted as solution A. Step S2: Preparation of hydrogel pregelation solution Tris(hydroxymethyl)aminomethane was dissolved in deionized water, and then a certain amount of sodium alginate was added to the solution. The mixture was vortexed and sonicated until the solution was homogeneous. The mass ratio of tris(hydroxymethyl)aminomethane to deionized water was 1:

4. Next, α-lipoic acid was added to the solution under stirring and sonication to obtain a yellow solution, wherein the mass ratio of deionized water to α-lipoic acid was 2:

1. Finally, a certain volume of ionic liquid was added to the α-lipoic acid solution and stirred for 3 minutes, which was recorded as solution B. Pour liquid B into a mold, heat it in an oven at 80°C for 1.5 hours, and then cool it to room temperature to form a pregel. Step S3: Formation of ion-conducting hydrogel The pregel obtained in step B above is uniformly dissolved in solution A and left for several days to promote the formation of uniform coordination sites. Then it is heated to evaporate excess water to form an ion-conducting hydrogel. In step S2, the mass ratio of α-lipoic acid to sodium alginate is (35~40):1; the molar ratio of α-lipoic acid to ionic liquid is (4~10):

1. In step S3, the molar ratio of α-lipoic acid to ferric ions is 1: (0.5%~5%).

2. The method for preparing the ion-conducting hydrogel according to claim 1, characterized in that: In step S1, the molar ratio of ferric nitrate nonahydrate to sodium citrate dihydrate is 1:

1.

3. The method for preparing the ion-conducting hydrogel according to claim 1, characterized in that: The ionic liquid in step S2 is one or more of 1-ethyl-3-methylimidazolium sulfate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium trifluoromethanesulfonate, and 1-butyl-3-methylimidazolium tetrafluoroborate.

4. The ion-conducting hydrogel prepared by the preparation method according to any one of claims 1-3.

5. The application of the ion-conductive hydrogel according to claim 4 in the fabrication of flexible wearable electronic sensors.

6. The application according to claim 5, characterized in that: The prepared ion-conductive hydrogel was cut into a rectangular shape, directly adhered to human skin, and then connected to electrodes for large and small-scale motion detection of the human body.